Surfaces and their measurement - Whitehouse, D. J. (David J.)
The importance of surface metrology has long been acknowledged in manufacturing and mechanical engineering, but has now gained growing recognition in an expanding number of new applications in fields such as semiconductors, electronics and optics. Metrology is the scientific study of measurement, and surface metrology is the study of the measurement of rough surfaces. In this book, Professor David Whitehouse, an internationally acknowledged subject expert, covers the wide range of theory and practice, including the use of new methods of instrumentation.?